A major practicum report at Euro Swiss Food Inc., Yakal St. San Antonio Village, Makati City - Japson, Cecilia Deligero (2006)
A 288-hr plant was conducted from April 19-May 22, 2007 at Euro Swiss Food Processing. The company is known for producing high quality sausages, cold cuts, and hams. It also served as venue for the application of knowledge in food processing learned from the academe and for gaining experience on the processing techniques used in the company, particularly in materials receiving, processing line operations, and product marketing. Technical analysis of the entire plant operations and some problems related to food processing were identified, documented, and provided with recommendations to help improve the plant operation. The actual involvement to the company?s operation provided opportunity to experience the real life in the food industry as well as developed interpersonal relationship among co-workers